Возможности двухпрофильного контроля конических прямозубых колес - Русецкий, В. Н.; Антонюк, В. Е. (НТУ "ХПИ", 2013)
Изложен метод двухпрофильного контроля конических прямозубых передач. Для реализации этого метода контроля разработана схема измерительных и образцовых конических зубчатых колес. Приведены рекомендации по реализации двухпрофильного метода контроля в условиях массового производства с использованием средств с записывающими устройствами

The method of It is offered for conic wheels with direct teeth to use modern means of the two-profile control with recorders. The scheme of measuring and exemplary conic cogwheels is developed for realization of this quality monitoring. Recommendations about realization of a two-profile quality monitoring of conic transfers in the conditions of mass production are resulted
Keywords: коническое зубчатое колесо; метод записи; точность; измерительное колесо; червячные передачи; bevel gear; precision; measuring wheel; two-profile control; recording method